2013
DOI: 10.1186/1472-6939-14-38
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and ethical perception regarding organ donation among medical students

Abstract: BackgroundTo determine the knowledge and ethical perception regarding organ donation amongst medical students in Karachi- Pakistan.MethodsData of this cross sectional study was collected by self administered questionnaire from MBBS students of Ziauddin University from 2010 to 2011. Sample size of 158 (83 First years and 75 Fourth years) were selected by convenient sampling and those students who were present and gave consent were included in the study. The data was analyzed by SPSS version 20.ResultsA total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
68
3
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 30 publications
12
68
3
7
Order By: Relevance
“…Regarding organs that can be donated, high awareness was observed regarding kidney, eye and liver donations ( Table 1). In comparison to our study, higher percentage of the final year medical students was aware about most of the organs being donated in the study by Ali et al [6]. In a similar study by Karini et al 26% of the participating medical students were aware of the organs that can be donated [14].…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Regarding organs that can be donated, high awareness was observed regarding kidney, eye and liver donations ( Table 1). In comparison to our study, higher percentage of the final year medical students was aware about most of the organs being donated in the study by Ali et al [6]. In a similar study by Karini et al 26% of the participating medical students were aware of the organs that can be donated [14].…”
Section: Discussioncontrasting
confidence: 45%
“…The interns in the present study were aware of live organ donations (48%) as well as donation following cardiac death (34%). Ali et al in a study carried out in Karachi, Pakistan reported that 59.2% of medical professionals participating in the study believed that ideal organ donor was a cardiac-dead person and 36.1% believed it was a living person [6]. 17.7% believed that a donor is a brain-dead person.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However contrary to our findings, In a study conducted by Ali et al and Alex et al, it was found that kidney was the most commonly donated organ, followed by others like heart, blood, cornea and liver. 17,18 The most common source of information on organ donation was media in our study followed by relatives and friends. Similar to the findings of our study, Sucharita et al, Saleem et al, Khan et al and Alghanim have found media (Television) as the major source of information among study participants.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Our study participants endorsed higher awareness about cornea as well as kidney donation in relation to other studies among medical undergraduates, postgraduate students and professionals. 19,20,23 Other aspects of the study like chances of success of split liver transplant as well as transplantation of adult liver into pediatric patients, use of genetically modified animal organs and need for lifelong antirejection treatment posttransplant were not explored in the available published literature worldwide and so could not be compared. 23 In our study comparatively lower awareness (49.69%) was recorded regarding importance of time factor for organ preservation and transplantation than another study conducted among the medical students in Pakistan.…”
Section: Discussionmentioning
confidence: 99%